Pengaruh Penambahan Serat Batang Pisang Kepok (Musa Pasadisianca) Terhadap Kuat Tekan Batako - Muhammad Andrean Bintara Adyanto; Gatut Rubiono; Ikhwanul Qiram (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2022)
Research has been carried out with the aim of obtaining the effect of adding